Research on the application of multimedia network technology in speed skating treaching - Qiansheng, J.; Qi, H. (Frontiers in Sport Research, 2020)
With the improvement of China's education level and the development of information networks, the application of multimedia network technology in speed skating teaching has also become more feasible. Speed skating teaching can improve the students' physical fitness and promote the development of students' physical and mental health. The application of multimedia network technology in the process of speed skating teaching can better improve the application effect and continuously promote the progress of students. Based on these opinions, this paper analyzes the methods of applying multimedia network technology in speed skating teaching, hoping that it will be beneficial to reality.